R&D cooperation and industry cartelization - Jacek Prokop; Adam Karbowski (Kiel Institute for the World Economy (IfW), 2013)
The objective of this paper is to investigate the impact of R&D cooperation on cartel formation in the product market. The R&D investments that precede the production process are aimed at the reduction of the unit manufacturing costs, and could create positive externalities for the potential competitors. In contrast to the preceding literature, we assume that the competition between firms on the product market takes place according to the Stackelberg leadership model. For simplicity we focus on the case of duopoly. Numerical analysis shows that a closer cooperation at the R&D stage may strengthen the incentives to create a cartel in the product market.
Keywords: O31; L41; L13; 330; R&D cooperation of firms; industry cartelization; Stackelberg competition